PENINGKATAN KREATIVITAS MAHASISWA MELALUI PEMBELAJARAN TRAINING MODEL DAN PORTOFOLIO - Yuliarma -- (Jurnal Pendidikan dan Kebudayaan, 2010)
The formulation of research subject is to determine if the student creativity can be improve through training model studies and portfolio examination in the making of fashion design modification in traditional attire major. The purpose of the research is to discover that the training model study method and portfolio examination can improve the student learning creativity in the tradition apparel major. These developments are class action research, which was held in 3 cycles, the actions were completed by training model method application and portfolio examination. In each cycles, the application of training model method and portfolio examination were given twice, with 3 times schools practice, 3 times homework’s and 3 evaluations. The research was held at KK FT UNP faculty. The instruments used are observation guide, interview guide and test. The result shows that the average of student creativity and learning process can be improved through training and portfolio studies. Each cycles display student creativity improvement, with the average score of the 1 cycle of design fashion illustration practice 1.70, 2nd cycle 2.27, 3rd cycle 3.19; decorative variation design 1st cycle 1.33, 2nd cycle 2.34, and 3 cycle 3.17; drawing presentation practice 1st cycle 1.27, 2nd cycle 2.26, and 3rd cycle 3.23. ABSTRAKRumusan masalah penelitian adalah Apakah kreativitas mahasiswa dapat ditingkatkan melalui pembelajaran training model dan penilaian portofolio dalam pembuatan desain busana modifikasi pada mata kuliah busana daerah. Penelitian bertujuan untuk mengungkapkan bahwa metode pembelajaran training model dan penilaian portofolio dapat meningkatkan kreativitas belajar mahasiswa pada mata kuliah busana daerah. Pengembangan ini merupakan penelitian tindakan kelas, dilaksanakan 3 siklus, tindakan dilakukan dengan penerapan metode pembelajaran training model dan penilaian portofolio. Pada setiap siklus, penerapan metode training model dan penilaian portofolio diberikan selama 2 kali pertemuan, dengan 3 kali tugas latihan di sekolah dan 3 kali latihan di rumah dan 3 kali penilaian. Penelitian dilaksanakan di jurusan KK FT UNP. Instrumen yang digunakan adalah pedoman observasi, pedoman wawancara, dan tes. Hasil penelitian rata-rata kreativitas dan hasil belajar mahasiswa dapat ditingkatkan melalui pembelajaran training dan portofolio. Pada setiap siklus terdapat peningkatan kreativitas mahasiswa.